Magnetic, electrical, and physical properties evolution in Fe3O4 nanofiller reinforced aluminium matrix composite produced by powder metallurgy method - Ashrafi, Negin; Mohamed Ariff, Azmah Hanim; Jung, Dong Won; Sarraf, Masoud; Foroughi, Javad; Sulaiman, Shamsuddin; Hong, Tang Sai (Multidisciplinary Digital Publishing Institute, 2022)
An investigation into the addition of different weight percentages of Fe3O4 nanoparticles to find the optimum wt.% and its effect on the microstructure, thermal, magnetic, and electrical properties of aluminum matrix composite was conducted using the powder metallurgy method. The purpose of this research was to develop magnetic properties in aluminum. Based on the obtained results, the value of density, hardness, and saturation magnetization (Ms) from 2.33 g/cm3, 43 HV and 2.49 emu/g for Al-10 Fe3O4 reached a maximum value of 3.29 g/cm3, 47 HV and 13.06 emu/g for the Al-35 Fe3O4 which showed an improvement of 41.2%, 9.3%, and 424.5%, respectively. The maximum and minimum coercivity (Hc) was 231.87 G for Al-10 Fe3O4 and 142.34 G for Al-35 Fe3O4. Moreover, the thermal conductivity and electrical resistivity at a high weight percentage (35wt.%) were 159 w/mK, 9.9 × 10−4 Ω·m, and the highest compressive strength was 133 Mpa.